Efek Park Therapy terhadap Kondisi Fisiologis dan Psikologis Mahasiswa Tingkat Akhir (Studi Kasus: Tebet Eco Park, Jakarta Selatan, DKI Jakarta) - Mangetan, Liana Irene; Pratiwi, Prita Indah; Budiarti, Tati (Jurnal Lanskap Indonesia, 2026)
Students often feel pressured and have difficulty because they have to meet high academic demands, this triggers a decline in psychological and physiological conditions. Methods that can be used to prevent this are by doing therapy in the open, one of which is park therapy. This study aims to examine the physiological and psychological effects of sitting and walking activities on final year. The sitting and walking activities were carried out in three places, a densely built road, the northern and southern parts of Tebet Eco Park. Data conducted by administering questionnaires to research subjects using a purposive sampling. The psychological questionnaires used were Perceived Stress Scale questionnaire (PSS-10), State-Trait Anxiety Inventory (STAI), Profile of Mood States (POMS-35), Oxford Happiness Questionnaire (OHQ), perceptions and preferences for garden elements and views. Data analyzed using validity and reliability, normality, repeated measures ANOVA, Friedman and paired sample t-tests. The results showed that the park therapy experiment carried out with two activities was significant in reducing blood pressure, stress and anxiety level, negative emotions and increasing positive emotion, level of happiness for final year university students who took part in the experiment (sig < 0, 05). Based on the analysis the time factor and the interaction between location and time had the most significant influence on physiological and psychological conditions. The addition of water elements, bird attracting plants, aromatic plants can provide a relaxing effect and are used as recommendations to support park therapy activities for the physiological and psychological benefit of the community.